Ethics of “homo informaticus” in the information environment (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The concept of homo informaticus emerged as a philosophical and anthropological response to the transformation of human ontology under the conditions of exponential growth in digital technologies and global information networks. The term emphasizes the emergence of a new type of personality — a subject whose identity, behavior, and modes of thinking are shaped by continuous involvement in the processes of collecting, processing, redistributing, and generating information.The ethical dimension of this “digitized” existence significantly determines the future of the citizen who is expected to build a radically new society. Therefore, we aim to emphasize the growing impact of the information society on the behavioral and practical aspects of the human citizen.
Keywords: Homo Informaticus, information ethics, digital human, information environment